Service Quality, Patient Satisfaction and Covid-19 Protection: It’s Impact on Patient’s Behavioral Intention to Visit the Hospital in Jakarta - Amelia Gianina Widjaja; Hendra Achmadi (Budapest International Research and Critics University, 2022)
The COVID-19 pandemic has substantially transformed Indonesia's healthcare visits and practices with new regulations to reduce the visitor flow and screen potential COVID-19 patients. The enforcement of the prevention regulations may alter patients' intention to visit the hospital to some extent. This paper examines the impact of service quality, patient satisfaction, and COVID-19 protection on patient behavioral intention to visit the hospital in Jakarta. This research is a quantitative study where we collected data from 160 patients who had visited the hospital in Jakarta using an online questionnaire during the COVID-19 pandemic. Factor analysis and the structural equation model were analyzed using PLS-SEM of how service quality, patient satisfaction, and COVID-19 protection impact behavioral intention. This study found that COVID-19 protection and patient satisfaction positively and significantly affect behavioral intention, as shown by the T-statistics value of 3.652 and 5.812, respectively. In contrast, we found no significant impact of service quality on behavioral intention. In conclusion, hospital management better adapts COVID-19 prevention policies and enhances patient satisfaction since it profoundly influences the patient’s behavioral intention to visit the hospital during the COVID-19 pandemic.